The Malaysian Cataract Surgery Registry: risk Indicators for posterior capsular rupture. Issue 11 (14th March 2017) - Salowi, Mohamad Aziz; Chew, Fiona L M; Adnan, Tassha Hilda; Ismail, Mariam; Goh, Pik-Pin
Abstract : Aim: To identify the risk indicators for posterior capsular rupture (PCR) in the Malaysian Cataract Surgery Registry (CSR). Methods: Data from the web-based CSR were collected for cataract surgery performed from 2008 to 2013. Data was contributed by 36 Malaysian Ministry of Health public hospitals. Information on patient's age, ethnicity, cause of cataract, ocular and systemic comorbidity, type of cataract surgery performed, local anaesthesia and surgeon's status was noted. Combined procedures and type of hospital admission were recorded. PCR risk indicators were identified using logistic regression analysis to produce adjusted OR for the variables of interest. Results: A total of 150 213 cataract operations were registered with an overall PCR rate of 3.2%. Risk indicators for PCR from multiple logistic regression were advancing age, male gender (95% CI 1.04 to 1.17; OR 1.11), pseudoexfoliation (95% CI 1.02 to 1.82; OR 1.36), phacomorphic lens (95% CI 1.25 to 3.06; OR 1.96), diabetes mellitus (95% CI 1.13 to 1.29; OR 1.20) and renal failure (95% CI 1.09 to 1.55; OR 1.30). Surgical PCR risk factors were combined vitreoretinal surgery (95% CI 2.29 to 3.63; OR 2.88) and less experienced cataract surgeons. Extracapsular cataract extraction (95% CI 0.76 to 0.91; OR 0.83) and kinetic anaesthesia were associated with lower PCR rates. Conclusions: This study was agreed with other studies for the risk factors of PCR with the exception of local anaesthesia given and type of cataract surgery. Better identification of high-risk patients for PCR decreases intraoperative complications and improves cataract surgical outcomes.